Preclinical in vivo evaluation of a gonococcal multivalent vaccine containing antigens identified by CASS - Roe, Shea K.; Zheng, Bo; Gulati, Sunita; Genco, Caroline; Ram, Sanjay; Massari, Paola (Frontiers in Immunology, 2025)
BackgroundNeisseria gonorrhoeae, causative agent of the human sexually transmitted infection gonorrhea, is a significant global health concern because of increasing antimicrobial resistance and the lack of an effective vaccine. Recent ecological analyses have shown a reduced incidence of gonorrhea in recipients of detergent-extracted outer membrane vesicle (OMV)-containing meningococcal vaccine, which has contributed to identification of shared, protective antigens. Previously, our group has developed an immunobioinformatics-based pipeline (CASS, Candidate Antigen Selection Strategy) for identification of gonococcal hypothetical proteins expressed during human natural mucosal infections, as novel vaccine candidates.MethodsIn this study, we expanded the immunological characterization of three targets, NGO0690, NGO0948 and Csp (copper storage protein, previously called NGO1701) to include analysis of their efficacy in a mouse model of gonococcal vaginal infection when combined as a trivalent subunit vaccine and adjuvanted with Alum and MPLA.ResultsWe reported induction of systemic and mucosal antibody responses, serum bactericidal activity against heterologous N. gonorrhoeae strains, and accelerated bacterial clearance in vivo. Immune profiling revealed a balanced Th1/Th2 response, based on IgG antibody subclasses and cytokines. Antigen dose de-escalation experiments in female and male mice showed sustained antibody production against the individual antigens and against whole bacteria. The latter were slightly lower than with the original dose vaccine particularly in male mice, who also exhibited a distinct cytokine pattern and weaker complement-mediated serum bactericidal activity (SBA) titers compared to female mice. These findings underscore the importance of considering sex-based differences in vaccine evaluation. A bivalent vaccine containing only NGO0690 and Csp was still protective in vivo, supporting the value of multivalent approaches to address gonococcal antigenic diversity.DiscussionOverall, our results suggested that the rational design of our multi-antigen subunit vaccines holds translational potential for enhancing broadly protective immune responses and protection against N. gonorrhoeae.